Child Safeguarding Policies in the Serbian Orthodox Church - Jović, Rastko (Religion and Children's Rights, 2025)
Abstract:In the face of recent shifts in perspective, this paper explores the general stance of Orthodox Christianity towards human rights. Although Orthodox theology has been perceived as unsupportive of human rights, recent theologians have shown more positive engagement, signalling a shift in the Church’s stance. This text tries to distil the theological importance given to children in the life of the early Church, while considering the canonical tradition of the Orthodox Church — which is attempting to align itself with the Convention on the Rights of the Child. The paper also discusses critical documents reflecting the Church’s perspective on human rights, acknowledging convergence with Church teachings, and addressing areas for improvement. Documents issued by some Orthodox churches – dealing with issues of human rights and the rights of children – explicitly stressed the significance of safeguarding children’s rights while simultaneously stressing the rights and dignity of the family. The dialectic expressed within these documents safeguards the balance between children’s rights and family dignity. The paper also emphasises the relevance of the family as the foundation of society, where members are willing to make sacrifices for one another, crucial for political and ethical intersections. The destruction of the family could lead to the separation of people from any form of collective identity, exposing society to forces that could ultimately empty individuals of their selves, leaving children with no more authentic identity that can be protected.Keywords: children, Human Rights, Orthodox Church, family, theology, baptism